The Concept of Makharij al-Ḥurūf in the Literature of 'Ilm al-Aṣwāt: Between Tajwīd Prescription and Modern Linguistic Description - Intan Muflihah (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to conduct a systematic literature review regarding the concept of makhārij al-ḥurūf (articulation points of Arabic letters) in traditional tajwīd literature and compare it with modern phonetic and phonological descriptions. The research method used is a qualitative descriptive analysis with a historical and comparative approach, examining classical tajwīd books such as Al-Muqaddimah fīmā Yajibu ‘alā Qāri’ al-Qur’ān by Ibn al-Jazarī, and contemporary linguistic works like Mu'jam al-Aṣwāt al-‘Arabiyyah by ‘Abd al-Ṣabūr Shāhīn. The findings indicate that the makhārij classification in tajwīd literature, which is divided into five main locations (jawf, ḥalq, lisān, shafatān, khayshūm), is primarily prescriptive and aimed at ensuring correct Qur'anic recitation. In contrast, modern linguistic studies offer a more detailed anatomical and acoustic description, recognizing more than 17 specific articulation points and incorporating spectrographic analysis. This research concludes that the tajwīd tradition possesses a robust empirical phonetic foundation that aligns in many aspects with modern science, although differences in orientation—perfection of worship versus scientific objectivity—result in distinct descriptive frameworks. The integration of both approaches can enrich the teaching of Arabic phonetics and tajwīd science.